If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -19 = 3x + 9 Reorder the terms: -19 + 4x = 3x + 9 Reorder the terms: -19 + 4x = 9 + 3x Solving -19 + 4x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -19 + 4x + -3x = 9 + 3x + -3x Combine like terms: 4x + -3x = 1x -19 + 1x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -19 + 1x = 9 + 0 -19 + 1x = 9 Add '19' to each side of the equation. -19 + 19 + 1x = 9 + 19 Combine like terms: -19 + 19 = 0 0 + 1x = 9 + 19 1x = 9 + 19 Combine like terms: 9 + 19 = 28 1x = 28 Divide each side by '1'. x = 28 Simplifying x = 28
| -9=u-2 | | 12k+6k^2+k^3+8=64 | | 3a+3=5s-7 | | x(x-3)(x-3)=4.8 | | Cos(2x)-3cos(x)-1=0 | | x=3-28 | | 3f-6=2t+2 | | 2i-3=i+14 | | 4x+5=-2x+5 | | 5+6x=x+7 | | (4x+6)+(-5x+2)= | | 2=6x+13x-6 | | 26-n=11 | | z^2+3*z+6=0 | | =13000 | | 4x-7=3(2x+5)-2 | | x^6+7x^5+21x^4+35x^3+35x^2+21x=1064640 | | a=3.14*d | | In(x-1)+(x+2)=1 | | x^3-9x-400=0 | | x+10=61 | | Y+3x=28 | | 3=v-5/3 | | 2sin(2teida)=0 | | (x+7)(2x-7)=0 | | 2x-3=0.5x | | 4(3z-1)-5(z+6)=4(z+1) | | (12-3x)/(2sqrt(6-x)=0 | | (12-3x)/(2√(6-x))=0 | | 18=r+16 | | d=8+4 | | 28+-28+30m= |